Metal Segregation in Bimetallic CoPd Carbide Carbonyl Clusters: Synthesis, Structure, Reactivity and Electrochemistry of [H6−nCo20Pd16C4(CO)48]n− (n=3–6). Issue 12 (2nd October 2013) - Ciabatti, Iacopo; Fabrizi de Biani, Fabrizia; Femoni, Cristina; Iapalucci, Maria Carmela; Longoni, Giuliano; Zacchini, Stefano
Abstract Nanometric CoPd bimetallic [H6−nCo20Pd16C4(CO)48]n− (n=3–6) tetracarbide carbonyl clusters have been prepared by redox condensation of [Co6C(CO)15]2− with [PdCl2(Et2S)2]. The crystal structures of both the dihydride tetra‐anion and monohydride penta‐anion have been determined as their [NEt4]4[H2Co20Pd16C4(CO)48]⋅4 CH3COCH3 and [NMe3(CH2Ph)][NMe4]4[HCo20Pd16C4(CO)48]⋅5 CH3COCH3 salts, respectively. The two species are isostructural and their structures display a perfect segregation of the two metals. They are composed of a cubic close‐packed (ccp) Pd16 core stabilised on its surface by four Co5C(CO)12 organometallic fragments. Their polyhydride nature has been corroborated by the study of their reactions with acids and bases, and confirmed by electrochemical studies. In addition, the reactions of [H2Co20Pd16C4(CO)48]4− with Na/naphthalene and PPh3/CO allowed the isolation of other lower nuclearity homoleptic and heteroleptic clusters, that is, [H6−nCo16Pd2C3(CO)28]n− (n=5, 6), [Co4Pd2C(CO)11(PPh3)2], [Co2Pd5C(CO)8(PPh3)5], and [Co4Pd4C2(PPh3)4(CO)10Cl]−. [H6−nCo16Pd2C3(CO)28]n− (n=5, 6) represent the first homoleptic metal–carbonyl clusters containing three interstitial carbide atoms.